Exposure‐Response Modeling and Simulation to Support Human Dosing of Botulism Antitoxin Heptavalent Product. Issue 1 (16th May 2022) - Beliveau, Martin; Anderson, Deborah; Barker, Doug; Kodihalli, Shantha; Simard, Emilie; Hall, Christine; Richardson, Jason S.
Abstract : Botulism antitoxin heptavalent (A, B, C, D, E, F, and G – Equine; BAT) product is a sterile solution of F(ab')2 and F(ab')2 ‐related antibody fragments prepared from plasma obtained from horses that have been immunized with a specific serotype of botulinum toxoid and toxin. BAT product is indicated for the treatment of symptomatic botulism following documented or suspected exposure to botulinum neurotoxin serotypes A to G in adults and pediatric patients. Pharmacokinetic and exposure‐response models were used to explore the relationship between BAT product exposure and the probability of survival, and the occurrence of relevant moderate clinical signs observed during the preclinical development of BAT product to justify the clinical dose. The predicted probability of survival in humans for all serotypes of botulinum neurotoxin was more than 95.9% following intravenous administration of one vial of BAT product. Furthermore, this BAT product dose is expected to result in significant protection against clinical signs in human adults for all botulinum neurotoxin serotypes. Our exposure response model indicates that we have sufficient antitoxin levels to give full protection at various theoretical exposure levels and, based on neutralization capacity/potency of one dose of BAT product, it is expected to exceed the amount of circulating botulinum neurotoxin.